ĮMONĖS RESTRUKTŪRIZAVIMO VYKSTANT BANKROTO PROCEDŪRAI SAMPRATA - Lazko, Svetlana (Teisė, 2015)
The article deals with the features of enterprise restructuring in bankruptcy. Ukrainian and foreign scientific literature, periodicals and materials existing legislation are analyzed. We have investigated the concept, analyzed the common signs of enterprise restructuring, as well as specific properties that reflect the essence of restructuring in bankruptcy. Special attention is paid to this form of restructuring as a division of the debtor to transfer debt to third parties not subject to rehabilitation. On the basis of these features suggested a definition of enterprise restructuring in bankruptcy.